On the metallurgical joining mechanism during ultrasonic spot welding of NiTi using a Cu interlayer. (15th March 2020) - Zhang, Wei; Ao, Sansan; Oliveira, J.P.; Li, Chunjie; Zeng, Zhi; Wang, Anqi; Luo, Zhen
Abstract: Ultrasonic spot welding of NiTi shape memory alloy with Cu interlayer was performed to understand the metallurgical joining mechanism at the materials' interface. Dynamic recrystallization of the Cu foil and high strain rate of the process induced a nano-scale transition layer composed of NiTiCu phase. The formation of this new phase occurs due to the frictional heating and shear deformation that is imposed by the ultrasonic vibration and contributes to the metallurgical bonding between the parent materials. Mechanical tension tests revealed that the joint with Cu interlayer presents enhanced strength. Graphical abstract: Image, graphical abstract